Activity Clinic and Affects in Workplace Conflicts: Transformation through transferential activity - Scheller, Livia (Outlines. Critical Practice Studies, 2014)
This paper presents some reflections about an approach in work psychology: the Activity Clinic. After a brief introduction to the conceptual background of the “Activity Clinic”, it covers three deeply interconnected themes. The first concerns the meaning attributed to the development of the affects present in the work situation under analysis; the second discusses the reasons for the conflicts that are ultimately due to these affects; the third considers how a method of co-analysis of the activity can lead towards transformation of those conflicts. Our reflections refer to the process engendered by this methodological approach as one of “transferential activity”. The paper explains this process by empirically describing the “transport” of affects involved in the conflicts. The personal interpretation of the cause of problems gives way to the understanding that they are due to organizational dysfunction rather than to individual personalities. Measures can then be taken to break the deadlocks experienced both at the personal and collective level.